The Effect of the Pancasila Student Profile Strengthening Project to Improve Student Entrepreneurial Competence - Hidayat, Rahmat; Effendi, Mawardi; Bentri, Alwen; Hidayati, Abna (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
In this research, the focus was on evaluating the impact of the Pancasila Student Profile Strengthening Project on enhancing the entrepreneurial competence of students at SMAN 1 Pasaman. Utilizing the quantitative survey method, the study targeted grade X students, encompassing 150 respondents from SMA Negeri 1 Pasaman, employing purposive sampling. Data collection involved distributing questionnaires both directly and online to students. The findings indicated a significant and positive correlation between the P5 program and the enhancement of entrepreneurial competence among secondary school learners. The study underscored the pivotal role of integrating Pancasila values into education, elucidating how it contributes to cultivating robust character traits and fostering independence crucial for future entrepreneurial endeavors. By emphasizing the Pancasila values within the educational framework, the research revealed its instrumental role in shaping students' attitudes and competencies, establishing a foundation for their potential engagement in entrepreneurial activities.